2006
DOI: 10.1111/j.1600-0684.2006.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of zona hardening in non‐human primate oocytes cultured in protein‐free medium

Abstract: These results indicate that fertilization failure occurs when macaque oocytes are cultured in medium without protein, but can be prevented with PVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Bovine serum albumin used in early studies (Xu, 2009a) was replaced by human serum protein supplement (SPS; Xu, 2010, 2011a) for relevance to future clinical application. The culture media also contains fetuin, a major glycoprotein in serum and follicular fluid, which reportedly prevents “hardening” of the zona pellucida in a serum-free culture environment (VandeVoort, 2007; Schroeder, 1990). Bovine fetuin is used currently due to unavailability of human protein.…”
Section: D Culture Of Macaque Folliclesmentioning
confidence: 99%
“…Bovine serum albumin used in early studies (Xu, 2009a) was replaced by human serum protein supplement (SPS; Xu, 2010, 2011a) for relevance to future clinical application. The culture media also contains fetuin, a major glycoprotein in serum and follicular fluid, which reportedly prevents “hardening” of the zona pellucida in a serum-free culture environment (VandeVoort, 2007; Schroeder, 1990). Bovine fetuin is used currently due to unavailability of human protein.…”
Section: D Culture Of Macaque Folliclesmentioning
confidence: 99%
“…On the other hand, a setback in biopsying thawed embryos is the hardening of zona pellucida due to freezing and thawing [24] probably because of irreversible denaturation of some unidentified proteins located in the zona. However, assisted hatching [25] or culturing embryos in protein-free medium [26] may improve implantation rates lowered due to zona hardening. The small hole that must be created in the zona for embryo biopsy after thawing may also help the embryo to hatch.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc sulphate incorporated in zinc PVA has been shown to selectively concentrate viable Cryptosporidium oocysts in the floatation technique (Bukhari and Smith 1995). PVA is widely used in cell culture and tissue engineering and it has been shown to improve the extracellular conditions for cell survival (Cheng and LeDuc 2006;Vandevoort et al 2007). Concerning aqueous potassium dichromate, a concentration of 2-2.5 % at 22°C provides the optimum laboratory conditions for sporulation of Cyclospora, Isospora and Eimeria oocysts.…”
Section: Discussionmentioning
confidence: 99%
“…Saavedra et al (2003) reported that PVA in cell culture promotes preservation of long-term hepatocytic functions. Vandevoort et al (2007) reported that in vitro maturation of the female ovarian oocysts cultured in a medium enriched with PVA was significantly better than cultures without PVA and the incidence of fertilisation and embryo development to blastocyst stage was better. Moreover, Deters et al (2003) found that zinc sulphate, a constituent of zinc PVA, is a potent stimulator for keratinocyte differentiation and increased cell proliferation in vitro.…”
Section: Discussionmentioning
confidence: 99%